Inflammasome activation and metabolic remodelling in p16‐positive aging cells aggravates high‐fat diet‐induced lung fibrosis by inhibiting NEDD4L‐mediated K48‐polyubiquitin‐dependent degradation of SGK1 - Gu, Xin; Meng, Haoyu; Peng, Chengyi; Lin, Shiyu; Li, Baihong; Zhao, Lin; Yang, Xue; Wang, Guangyan; Cai, Wenyuan; Zhou, Jiawen; Liu, Shuiyuan; Wu, Peng; et al. (Clinical and translational medicine, 2023)
Background Chronic changes caused by a high‐fat diet (HFD) may be associated with weakened lung function in obese patients. However, few studies have focused on the role of senescent cells in HFD‐induced pulmonary fibrosis. This study aimed to determine whether (i) obesity causes the accumulation of aging cells in the lungs, (ii) p16 accumulation in aging epithelial cells or fibroblasts exacerbates long‐term HFD‐induced senescence‐associated pulmonary fibrosis (SAPF) and (iii) p16 deletion or clearance of aging cells ameliorates HFD‐induced SAPF through inactivation of the inflammasome and metabolic remodelling. Methods Twelve‐month old male mice of p16INK4a (hereafter p16) knockout (p16−/−) and wild‐type (WT), ApoE knockout (ApoE−/−) and ApoE−/−p16−/− were fed a HFD to induce obesity, and the effects of treatment with the senolytic drug ABT263 or the SGK1 specific inhibitor EMD638683 on fibrosis, inflammaging, gene expression, integrin‐inflammasome signalling and metabolism were examined. A549 and IMR‐90 cells were transduced with p16‐overexpressing adenovirus, and treated with palmitic and oleic acids (P&O) to induce steatosis in vitro. Results We found that long‐term HFD promoted the expression of p16 and the increase of senescent cells in the lung. P16 knockout or ABT263 treatment alleviated pulmonary fibrosis, the increase of senescent cells and senescence‐associated secretory phenotype (SASP) in HFD‐fed mice, as well as in P&O‐treated A549 and IMR‐90 cells. RNA sequencing and bioinformatics analyses revealed that p16 knockout inhibited activation of the integrin‐inflammasome pathway and cellular glycolysis. Mass spectrometry, co‐immunoprecipitation and GST pull‐down assays demonstrated that p16 bound to the N‐terminal of SGK1, thereby interfering with the interaction between the E3 ubiquitin ligase NEDD4L and SGK1, and subsequently inhibiting K48‐polyubiquitin‐dependent degradation of SGK1 mediated by the NEDD4L–Ubch5 complex. EMD638683 was found to alleviate HFD‐induced pulmonary fibrosis and activation of the integrin‐inflammasome pathway. Conclusion P16 accumulation promoted activation of integrin– inflammasome pathway and cell glycolysis by binding to the N– terminal of SGK1, intefering with the interaction between the E3 ubiquitin ligase NEDD4L and SGK1, thereby inhibiting K48– polyubiquitin– dependent degradation of SGK1 mediated by the NEDD4L–Ubch5 complex. ABT263 or EMD638683 could be used as potential drugs to treat pulmonary fibrosis in obese patients. Following points are discussed. P16 accumulation promoted activation of the integrin‐inflammasome pathway and cell glycolysis by binding to the N‐terminal of SGK1. P16 interfered with the interaction between NEDD4L and SGK1, thereby inhibiting K48‐polyubiquitin‐dependent degradation of SGK1 mediated by the NEDD4L–Ubch5 complex. Clearance of senescent cells by administration of ABT263 or the SGK1‐specific inhibitor EMD638683 or SGK1 siRNA ameliorated HFD‐induced pulmonary fibrosis.